2017
DOI: 10.1007/s10620-017-4775-8
|View full text |Cite
|
Sign up to set email alerts
|

Liver Function Assessment Using Albumin–Bilirubin Grade for Patients with Very Early-Stage Hepatocellular Carcinoma Treated with Radiofrequency Ablation

Abstract: Among patients with very early-stage HCC treated with RF ablation, ALBI grade was a good stratifying biomarker. ALBI grade was better tool for assessing liver function than Child-Pugh score for very early-stage HCC treated with RF ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…Many scholars are gradually focusing on demographic and laboratory data, which are secure, repeatable, and easily available for predicting the recurrence of patients with HCC receiving only TACE or ablation therapy. Various studies showed that several predictors might indicate poor RFS, some of which are as follows: (1) noninvasive fibrosis markers such as aspartate APR index and age-to-platelet index; 13,14 (2) liver function markers such as albumin and albumin-to-bilirubin index; 15,16 (3) tumor-related markers such as tumor number, AFP, lens culinaris agglutinin-reactive fraction of AFP-L3, and des-gamma-carboxy prothrombin; [17][18][19] (4) inflammatory Abbreviations: RFA, radiofrequency ablation; MWA, microwave ablation; AHC, argon-helium cryoablation; HBV, hepatitis B virus; HCV, hepatitis C virus; ALD, alcohol liver disease; AFP, alpha-fetoprotein; ALT, alanine aminotransferase; AST, aspartate aminotransferase; γ-GT, gamma-glutamyltransferase; APR, albumin-to-prealbumin ratio, the APR was estimated as the albumin divided by the prealbumin. Abbreviations: RFA, radiofrequency ablation; MWA, microwave ablation; AHC, argon-helium cryoablation; HBV, hepatitis B virus; HCV, hepatitis C virus; ALD, alcohol liver disease; AFP, alpha-fetoprotein; ALT, alanine aminotransferase; AST, aspartate aminotransferase; γ-GT, gamma-glutamyltransferase; APR, albumin-to-prealbumin ratio, the APR was estimated as the albumin divided by the prealbumin.…”
Section: Discussionmentioning
confidence: 99%
“…Many scholars are gradually focusing on demographic and laboratory data, which are secure, repeatable, and easily available for predicting the recurrence of patients with HCC receiving only TACE or ablation therapy. Various studies showed that several predictors might indicate poor RFS, some of which are as follows: (1) noninvasive fibrosis markers such as aspartate APR index and age-to-platelet index; 13,14 (2) liver function markers such as albumin and albumin-to-bilirubin index; 15,16 (3) tumor-related markers such as tumor number, AFP, lens culinaris agglutinin-reactive fraction of AFP-L3, and des-gamma-carboxy prothrombin; [17][18][19] (4) inflammatory Abbreviations: RFA, radiofrequency ablation; MWA, microwave ablation; AHC, argon-helium cryoablation; HBV, hepatitis B virus; HCV, hepatitis C virus; ALD, alcohol liver disease; AFP, alpha-fetoprotein; ALT, alanine aminotransferase; AST, aspartate aminotransferase; γ-GT, gamma-glutamyltransferase; APR, albumin-to-prealbumin ratio, the APR was estimated as the albumin divided by the prealbumin. Abbreviations: RFA, radiofrequency ablation; MWA, microwave ablation; AHC, argon-helium cryoablation; HBV, hepatitis B virus; HCV, hepatitis C virus; ALD, alcohol liver disease; AFP, alpha-fetoprotein; ALT, alanine aminotransferase; AST, aspartate aminotransferase; γ-GT, gamma-glutamyltransferase; APR, albumin-to-prealbumin ratio, the APR was estimated as the albumin divided by the prealbumin.…”
Section: Discussionmentioning
confidence: 99%
“…HCC is the dominant form of primary liver cancer in patients with chronic liver disease and cirrhosis (2). Patients with early-stage HCC can be treated with surgery to remove part of the liver can undergo or transplantation, which contributes toward a 5-year survival rate of >70% (3). However, for the majority of patients with advanced-stage HCC whose disease is too advanced for them to undergo surgical treatment, the 5-year survival rate is extremely low at ~15% (4).…”
Section: Introductionmentioning
confidence: 99%
“…Among the present 115 naïve HCC patients who had multiple countable tumors (≤5) and unmet needs, hepatic function in the Comb group was worse as compared to that in the SR group when assessed by ALBI grade (ALBI grade 1: 42.4 vs. 64.6%, p = 0.034) as well as Fib-4 index (6.30 ± 5.34 vs. 3.75 ± 2.10, p = 0.019), whereas OS and DFS rates were not significantly different between the groups. In previous studies, ALBI grade has shown better prognostic predictive value as compared to Child-Pugh class for various therapeutic modalities, including surgical resection [29, 30], RFA [31, 32], TACE [33], and sorafenib [28], as well as in ALBI-T [14] and mALBI-T [10, 11] scores as total scoring systems. Clinical unmet needs such as those seen in our patients might be resolved by complementary use of low invasive RFA in combination with resection.…”
Section: Discussionmentioning
confidence: 99%